Intricate thicket : reading late modernist poetries - Scroggins, Mark, 1964- (Modern and contemporary poetics., 2015)
"In Intricate Thicket: Some Late Modernist Poetries, Mark Scroggins writes with wit and dash about a fascinating range of key twentieth- and twenty-first-century poets and writers. In nineteen lively and accessible essays, he persuasively argues that the innovations of modernist verse were not replaced by postmodernism, but rather those innovations continue to infuse contemporary writing and poetry with intellectual and aesthetic richness. In these essays, Scroggins reviews the legacy of Louis Zukofsky, delineates the exceptional influence of the Black Mountain poets, and provides close readings of a wealth of examples of poetic works from poets who have carried the modernist legacy into contemporary poetry. He traces with an insider's keen observation the careers of many of the most dynamic, innovative, and celebrated poets of the past half-century, among them Ian Hamilton Finlay, Ronald Johnson, Rae Armantrout, Harryette Mullen, and Anne Carson. In a concluding pair of essays, Scroggins situates his own practice within the broad currents he has described. He reflects on his own aesthetics as a contemporary poet and, drawing on his extensive study and writing about Louis Zukofsky, examines the practical and theoretical challenges of literary biography. While the core of these essays is the interpretation of poetry, Scroggins also offers clear aesthetic evaluations of the successes and failures of the poetries he examines. Scroggins engages with complex and challenging works, and yet his highly accessible descriptions and criticisms avoid theoretical entanglements and specialized jargon. Intricate Thicket yields subtle and multifaceted insights to experts and newcomers alike. "--